A McKay type bivariate beta distribution of third kind. Issue 4 (18th May 2020) - Jayakumar, G. S. David Sam; Sulthan, A.; Samuel, W.
Abstract: This paper proposes a new form of McKay type bivariate beta distribution of third Kind and the Univariate beta distribution of third kind are its marginal. Moreover, Conditional distributions and its moments of are derived. Similarly, Generating functions such as moment, Cumulant, characteristic functions are expressed in Kampé de Fériet function and Shannon's differential entropy are also determined. Moreover, the three-dimensional probability surfaces are used to visualize the shape of the derived densities graphically. Finally, its special cases are also discussed.